Mitochondrial DNA D-loop hypervariable regions: Czech population data - Vanecek, T; Vorel, F; Sip, M (International journal of legal medicine, 2004)
In order to identify polymorphic sites and to find out their frequencies and the frequency of haplotypes, the complete D-loop of mitochondrial DNA (mtDNA) from 93 unrelated Czech Caucasians was sequenced. Sequence comparison showed that 85 haplotypes were found and of these 78 were unique, 6 were observed twice and 1 was observed three times. Genetic diversity (GD) was estimated at 0.999 and the probability of two randomly selected sequences matching (random match probability, RMP) at 1.2%. Additionally these calculations were carried out for hypervariable regions 1, 2 (HV1, HV2), for the area between HV1 and HV2 and for the area of the hypervariable region HV3. The average number of nucleotide differences (ANND) was established to be 10.2 for the complete D-loop. The majority of sequence variations were substitutions, particularly transitions. Deletions were found only in the region where HV3 is situated and insertions in the same place and in poly-C tracts between positions 303 and 315 in HV2. A high degree of length heteroplasmy was found especially in the regions of poly-C tracts between positions 16184 and 16193 in HV1 and between positions 303 and 315 in HV2. Position heteroplasmies were found in two cases.
Keywords: Sequence Analysis, DNA; soudní lékařství; hypervariabilní oblasti; Česká republika; Genetic Variation; Complementarity Determining Regions; Genetics, Population; lidé; haplotypy; sekvenční analýza DNA; genetická variace; Czech Republic; Haplotypes; DNA, Mitochondrial; populační genetika; mitochondriální DNA; Forensic Medicine; Humans